Forging Qur'anic Character: A School Principal Leadership Model-Insights - Siti Muawanatul Hasanah; Agus Maimun; Marno Marno; Ahmad Barizi (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2024)
School principals are essential in shaping the Qur'anic character of the educational institutions they lead. This research is categorized as multi-case field research with data described descriptively. The main instrument of this research is the researcher, who explores data using three methods: interviews, observation, and documentation. The data analysis technique is carried out in two stages: individual case data analysis and cross-case data analysis. The researcher draws the following conclusions: First, the principal leadership model in two institutions: a) inclusive low profile model, b) social helpful model, and c) equilibrium structure model. Second, the school principal's strategic steps in forming Qur'anic character: a) integration of subjective spiritual and objective skills, b) implementation of organic spiritual collectivity strategies, and c) internalization of active, positive religiosity values. Third, students' Qur'anic character is formed through the leadership of the school principal: a) assimilation of spiritual values, b) exploration of dimensions of faith, c) contextualization of the Qur'an, d) planned disciplinary management, and e) religious inspiration in education This research provides the following theoretical implications: a) through the leadership model that is built, the principal, spiritual leader influences school culture in the formation of student character, b) the leadership model of the two school principals becomes a role model in the formation of students' Qur'anic character through the program. joint school activity program.